Transparent ultraviolet-proof composite film as well as preparation method and application thereof

By using a combination of acetylated lignin, elolite nanomaterials, chitosan and polyvinyl alcohol, a transparent and anti-ultraviolet composite film was prepared, which solved the problem of difficult to take into account both the ultraviolet pass rate and the visible pass rate in the prior art, and achieved the effect of high transparency and high mechanical properties.

CN119661961AActive Publication Date: 2025-03-21ZHEJIANG ACADEMY OF AGRICULTURE SCIENCES

Patent Information

Application Number
CN202411741100.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-21
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing ultraviolet anti-violet composite film with added lignin cannot guarantee that the ultraviolet light passing rate between wavelength 200-400nm is less than 5%, and the visible light passing rate between 400-780nm reaches more than 60%, and has high mechanical properties.

Method used

Acetylated lignin, eloline nanomaterial, chitosan and polyvinyl alcohol are used as raw materials. By loading acetylated lignin onto the eloline nanomaterial, mixed with chitosan and polyvinyl alcohol, and then sonication and film formation treatment, a transparent and ultraviolet-proof composite film is prepared.

Benefits of technology

It achieves high transparency with a UV pass rate between wavelengths 200-400 nm with a wavelength of less than 5% and a visible pass rate between 400-780 nm with a high transparency, and has high mechanical properties and good oxidation and hydrophobicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661961A_ABST
    Figure CN119661961A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of thin film materials, and particularly relates to a transparent ultraviolet-proof composite film as well as a preparation method and application thereof. The transparent ultraviolet-proof composite film provided by the invention is prepared from the following raw materials: acetylated lignin, a halloysite nano material, chitosan and polyvinyl alcohol, the acetylated lignin is loaded on the halloysite nano material. The specific transparent ultraviolet-proof composite film disclosed by the invention has high transparency on the basis of ensuring that the passing rate of ultraviolet light with the wavelength of 200-400nm is less than 5%, the passing rate of visible light with the wavelength of 400-780nm reaches more than 60%, and meanwhile, the transparent ultraviolet-proof composite film also has high mechanical property, is capable of blocking moisture and oxygen, is good in biological safety and is degradable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of film materials, and in particular relates to a transparent ultraviolet-proof composite film and a preparation method and application thereof. Background Art

[0002] With the change of people's modern lifestyle, consumers' demand for transparency of product information and packaging is increasing. Packaging has been widely used as the most convenient physical method to slow down the oxidation and corruption of materials. Ultraviolet rays can be divided into three bands according to different radiation wavelengths: UVA (320-400nm), UVB (280-320nm) and UVC (200-280nm). Among them, UVA and UVB bands have strong ultraviolet penetration, which is not only harmful to human body and organisms, but also accelerates the oxidation rate of food and the aging, degradation and fading of daily materials. Therefore, as people have a deeper understanding of the hazards of ultraviolet rays, anti-ultraviolet barrier packaging materials have become a research hotspot. Transparent anti-ultraviolet barrier packaging film is a packaging film composed of different types of polymers based on different applications. By adopting this packaging, while shielding ultraviolet rays, blocking moisture and isolating oxygen, food manufacturers can better show customers the freshness of their products as a means to increase sales. There are many types of common barrier packaging. For example, aluminum foil packaging has good barrier properties, but poor ductility and is prone to forming pinholes, resulting in reduced barrier properties. Opaque packaging such as kraft paper cannot be directly evaluated for its quality status. Ordinary plastic packaging has good air barrier properties and is transparent, but it comes from non-renewable petrochemical resources, is non-degradable, and has poor UV barrier properties. Under long-term exposure to ultraviolet light, the contents in the packaging bag absorb the energy of ultraviolet light, triggering an auto-oxidation reaction and accelerating the oxidation rate.

[0003] Lignin-based composite materials use lignin as a degradable filling material, which not only reduces the production cost of high molecular polymer materials, but also improves the hydrophobicity, anti-oxidation, antibacterial, UV shielding (UV shielding includes absorbing UV rays and reflecting and scattering UV rays to reduce the UV transmission rate. The physical structure of lignin has a shielding effect on UV rays through reflection and scattering. At the same time, the phenolic hydroxyl group, ketone carbonyl group and other functional groups in lignin have the ability to absorb UV rays. Together, lignin has good UV resistance), water vapor barrier and other properties. Chinese patent CN114474449B discloses a lignin / PBAT composite film material and its preparation method and application, using biodegradable lignin filler to reduce the production cost of PBAT and improve the tensile properties of composite materials. However, due to the high-temperature blending and hot pressing film used in this method, the condensation phenomenon of hot processing will lead to the aggregation of lignin, the color of the film will deepen, and the appearance will be poor.

[0004] Although lignin-based materials have been widely studied and applied, the above-mentioned films still have defects. The single-component natural lignin has complex and diverse functional groups, which gives it good full-band UV shielding properties, but it does not have film-forming properties, has poor barrier properties, and contains a large number of phenolic hydroxyl groups, which makes its color darker, greatly limiting its application in the field of food packaging. The existing addition of lignin can reduce the cost of polymer materials and has high UV shielding properties, but it still cannot guarantee that the visible light transmittance between 400-780nm reaches more than 60% (high transparency) on the basis of a UV transmittance between 200-400nm and less than 5%, while having high mechanical properties. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the existing anti-ultraviolet composite film with added lignin, which cannot ensure that the transmittance of visible light between 400-780nm reaches more than 60% (high transparency) on the basis of the ultraviolet light transmittance between 200-400nm being less than 5%, and has high mechanical properties, thereby providing a transparent anti-ultraviolet composite film and its preparation method and application.

[0006] The present invention provides a transparent UV-proof composite film, wherein the raw materials of the transparent UV-proof composite film include acetylated lignin, halloysite nanomaterial, chitosan and polyvinyl alcohol;

[0007] The acetylated lignin is loaded on the halloysite nanomaterial.

[0008] The present invention provides a method for preparing a transparent UV-proof composite film, comprising the following preparation steps:

[0009] 1) preparing acetylated lignin;

[0010] 2) loading the acetylated lignin prepared in step 1) onto a halloysite nanomaterial to obtain a halloysite nanocomposite;

[0011] 3) Mixing the halloysite nanocomposite prepared in step 2) with chitosan solution and polyvinyl alcohol solution, removing bubbles in the solution and then performing film-forming treatment to obtain the transparent UV-resistant composite film.

[0012] Preferably, step 2) comprises: mixing the halloysite nanomaterial, acetylated lignin and a solvent, and obtaining the halloysite nanocomposite after separation.

[0013] Preferably, in step 2), the halloysite nanomaterial and water are first mixed to form solution A, and then the acetylated lignin prepared in step 1) is dissolved in a dioxane aqueous solution to form solution B, and then solution B is added to solution A and mixed, and the solid is separated after ultrasonic treatment to obtain a halloysite nanocomposite;

[0014] Optionally, after the solid separation step, a drying step is also included;

[0015] Optionally, before performing step 2), the step of acidifying the halloysite nanomaterial is also included;

[0016] Optionally, before the halloysite nanomaterial and water are mixed, the method further includes placing the halloysite nanomaterial in a hydrochloric acid aqueous solution for ultrasonic pretreatment.

[0017] Optionally, when the halloysite nanomaterial is placed in a hydrochloric acid aqueous solution for ultrasonic pretreatment, the dosage ratio of the halloysite nanomaterial to the hydrochloric acid aqueous solution is (1-5): (400-500), in units of g:mL;

[0018] Optionally, the mass concentration of hydrochloric acid in the hydrochloric acid aqueous solution is 0.01-0.5 mol / L.

[0019] Optionally, the halloysite nanomaterial includes but is not limited to naturally or synthetically obtained flaky, blocky, and tubular halloysite in different forms; optionally, the halloysite nanomaterial is a halloysite nanotube.

[0020] Optionally, the step of placing the halloysite nanomaterial in a hydrochloric acid aqueous solution and ultrasonically pre-treating the material further comprises a drying step;

[0021] Optionally, the halloysite nanomaterial is placed in a hydrochloric acid aqueous solution and then subjected to ultrasonic pretreatment and then dried at 25-100° C. to remove moisture;

[0022] Optionally, the ultrasonic power of the halloysite nanomaterial in the hydrochloric acid aqueous solution for ultrasonic pretreatment is 25-300 W, and the ultrasonic pretreatment time is 0.5-2 h.

[0023] Preferably, the ratio of the halloysite nanomaterial to water in step 2) is 1:(10-100), in units of g:mL;

[0024] The dosage ratio of the acetylated lignin to the dioxane aqueous solution is 1:(10-100), in units of g:mL;

[0025] The volume ratio of dioxane to water in the dioxane aqueous solution in step 2) is (1-9): (1-5);

[0026] The mass ratio of the acetylated lignin in the solution B to the halloysite nanomaterial in the solution A is (1-5): (1-5);

[0027] The ultrasonic power of the ultrasonic treatment in step 2) is 25-300W, and the ultrasonic treatment time is 0.5-2h;

[0028] The stirring speed of adding solution B into solution A is 50-600 r / min, and the mixing time is 0.5-24 h.

[0029] Preferably, in step 3), the halloysite nanocomposite prepared in step 2) is mixed with a dioxane aqueous solution, homogenized, and then mixed with a chitosan solution, a polyvinyl alcohol solution and glycerol, and subjected to ultrasonic treatment to remove bubbles in the solution before film-forming treatment to obtain the transparent UV-resistant composite film.

[0030] The purpose of the homogenization in the present invention is to achieve a better dispersion effect. In addition to dispersion, ultrasound also has the function of removing bubbles in the solution, which is beneficial to film formation.

[0031] Preferably, the ratio of the halloysite nanocomposite to the dioxane aqueous solution in step 3) is 1:(40-60), in units of g:mL;

[0032] The volume ratio of dioxane to water in the dioxane aqueous solution in step 3) is (1-5): (1-5);

[0033] The homogenization time is 5-10 minutes, and the homogenization speed is 6000-24000r / min;

[0034] Optionally, the temperature of the homogenization treatment is 10-55°C, for example, the temperature of the homogenization treatment is room temperature.

[0035] Optionally, the ultrasonic power of the ultrasonic treatment in step 3) to remove bubbles in the solution is 25-300W, and the ultrasonic treatment time is 0.5-2h;

[0036] The dosage ratio of the halloysite nanocomposite to the chitosan solution is 1:(13-17), in g:mL;

[0037] The volume ratio of the chitosan solution, the polyvinyl alcohol solution and the glycerol is (13-17): (28-32): (0.1-0.3);

[0038] Optionally, the halloysite nanocomposite and the dioxane aqueous solution are mixed by ultrasound, the ultrasound power is 200-300 W, and the ultrasound time is 0.5-1.5 h;

[0039] Optionally, after homogenization, the mixture is stirred and mixed with chitosan solution, polyvinyl alcohol solution and glycerol, the stirring and mixing speed is 400-700 r / min, the stirring and mixing time is 10-14 h, and the stirring and mixing temperature is 10-45° C.;

[0040] Optionally, stir to combine at room temperature.

[0041] The chitosan content of the chitosan solution is 1-5% by mass;

[0042] The solvent in the chitosan solution is an acetic acid aqueous solution; the mass concentration of acetic acid in the acetic acid aqueous solution is 1-2%;

[0043] The mass content of polyvinyl alcohol in the polyvinyl alcohol solution is 2-6%;

[0044] The polyvinyl alcohol solution is a polyvinyl alcohol aqueous solution;

[0045] Optionally, the film forming process includes casting and drying.

[0046] The present invention does not specifically limit the film forming process, including but not limited to hot pressing melting, casting and the like. For example, the film forming process can be selected to include casting and drying.

[0047] Preferably, in step 1), lignin is added to a propionic anhydride / pyridine solution and stirred for reaction. After the reaction is completed, water is added and the solid is separated to obtain acetylated lignin.

[0048] Preferably, the dosage ratio of the lignin to the propionic anhydride / pyridine solution is 1:(11-15), in g:mL;

[0049] The volume ratio of propionic anhydride to pyridine in the propionic anhydride / pyridine solution is (2-5):10;

[0050] The stirring reaction speed is 400-600r / min, and the stirring reaction time is 20-26h;

[0051] Optionally, the volume ratio of water to propionic anhydride / pyridine solution is (200-500):(11-15).

[0052] The lignin includes but is not limited to natural or synthetic alkaline lignin, dealkalized lignin, modified lignin or lignin salts, and any lignin can be obtained commercially. (Lignin salts include sodium lignin salt and lignin sulfonate, etc., typically but not limited to calcium lignin sulfonate, sodium lignin sulfonate, etc.).

[0053] Optionally, after the solid separation step is completed, the solid is further washed with water and dried;

[0054] Optionally, the water washing is performed 2-4 times;

[0055] Optionally, in the water washing and drying steps, the drying temperature is 50-80° C. and the drying time is 10-30 hours.

[0056] The invention provides a transparent composite film capable of preventing ultraviolet rays, which is prepared by the method for preparing the transparent composite film capable of preventing ultraviolet rays.

[0057] The present invention provides an application of the transparent UV-proof composite film or the transparent UV-proof composite film prepared by the preparation method described above in UV-proof materials, such as UV-proof film materials.

[0058] The present invention provides an application of the transparent UV-proof composite film or the transparent UV-proof composite film prepared by the preparation method in food packaging materials.

[0059] The technical solution of the present invention has the following advantages:

[0060] The transparent UV-proof composite film provided by the present invention comprises raw materials including acetylated lignin, halloysite nanomaterial, chitosan and polyvinyl alcohol; the acetylated lignin is loaded on the halloysite nanomaterial. The acetylated lignin not only reduces the color of the original dealkalized lignin substrate, thereby significantly improving the transparency of the composite film; at the same time, the grafting of acetyl groups also increases the hydrophobicity and antioxidant properties of the film substrate, and at the same time, the presence of acetyl groups causes n→π* transition, although the ultraviolet light absorption capacity for the UVC band is weakened, but the ultraviolet absorption in the 320-400nm band is enhanced, and the transmittance of ultraviolet rays is reduced after the ultraviolet film substrate absorbs, thereby improving the ultraviolet shielding performance. Halloysite nanomaterials have the characteristics of large specific surface area, good adsorption, a large number of hydroxyl groups, negative charge on the outer surface, and absorption and reflection of ultraviolet rays. Halloysite nanomaterials are used to load acetylated lignin and combine with the positively charged chitosan. Electrostatic interaction promotes molecular redirection and increases the orderliness between molecules. After loading acetylated lignin, the problem of easy aggregation of acetylated lignin is effectively solved, compatibility is increased, and large aggregates of lignin disappear, further improving the transparency of the composite film. At the same time, the large number of hydroxyl groups contained in polyvinyl alcohol can form a strong hydrogen bond network structure with chitosan and halloysite nanomaterials, increase the interaction between molecules, and form a more dense and uniform composite film structure, with a more obvious shielding effect on ultraviolet rays, and can also reduce the aggregation of lignin molecules and improve the mechanical properties of the composite film. In addition, the excellent ultraviolet absorption performance of halloysite nanomaterials in the short-wave band has a synergistic effect with acetylated lignin, further enhancing the ultraviolet absorption of the composite film in the short-wave band. The transparent UV-proof composite film of the present invention has high shielding property for light with wavelength in the range of 200nm-400nm, and high transmittance for visible light (wavelength). On the whole, the specific transparent UV-proof composite film of the present invention has high transparency on the basis of ensuring that the UV light transmittance between wavelengths of 200-400nm is less than 5%, and the visible light transmittance between 400-780nm reaches more than 60%, and at the same time, it also has high mechanical properties, and is moisture-proof, oxygen-proof, biologically safe, and degradable.

[0061] 2. The transparent UV-proof composite film obtained by the specific preparation method of the present invention is biocompatible, is not easily damaged when used as a packaging material, and will not react with the packaging contents, is safe and environmentally friendly. Therefore, the transparent UV-proof composite film can be used as a food packaging material away from food or in contact with food. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0063] Figure 1 SEM images of dealkalized lignin and SEM images of acetylated lignin prepared in Example 1 of the present invention;

[0064] Figure 2 Fourier transform infrared spectroscopy (FT-IR) analysis comparison diagram of the composite films prepared in Example 1 of the present invention and Comparative Examples 1-3;

[0065] Figure 3 Comparison of the anti-ultraviolet performance of the composite films prepared in Example 1 of the present invention and Comparative Examples 1-4;

[0066] Figure 4 Photos of bending tests in different directions of the composite film prepared in Example 1 of the present invention;

[0067] Figure 5 Comparison chart of tensile strength and elongation of the composite films prepared in Example 1 of the present invention and Comparative Examples 1-3;

[0068] Figure 6 Comparative diagram of biodegradability of composite films prepared in Example 1 of the present invention and Comparative Example 1;

[0069] Figure 7 Comparison chart of biosafety experiments of composite membranes prepared in Example 1 of the present invention and Comparative Example 1;

[0070] Figure 8 A comparison chart of the actual colors of the composite films prepared in Examples 1-3 of the present invention and Comparative Examples 1-4. DETAILED DESCRIPTION

[0071] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0072] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0073] The halloysite nanotubes of the present invention can be obtained from conventional commercial sources. The halloysite nanotubes used in the examples and comparative examples of the present invention are from Guangzhou Runwo Materials Technology Co., Ltd., with a product number of 332-58-7;

[0074] The dealkalized lignin samples used in the examples and comparative examples of the present invention were purchased from Maclean, CAS: 9005-53-2.

[0075] Example 1

[0076] This embodiment provides a method for preparing a transparent UV-resistant composite film, comprising the following steps:

[0077] 1) 1 g of dealkalized lignin sample dried to constant weight was added to a 50 mL beaker, followed by the addition of 13 mL of propionic anhydride / pyridine (the volume ratio of propionic anhydride to pyridine was 3:10) solution, and the mixture was stirred at 400 r / min for 24 hours at room temperature. After the reaction was completed, 400 mL of distilled water was added, and a solid residue was obtained by centrifugation. The solid residue was washed three times with distilled water and vacuum dried at 60° C. for 24 hours to obtain acetylated lignin. 1 g of acetylated lignin was prepared according to this method for later use;

[0078] 2) 3 g of halloysite nanotubes were placed in a 500 mL beaker, 8 mL of 11.9 mol / L hydrochloric acid aqueous solution and 450 mL of water were added, and ultrasonic pretreatment was performed at 150 W for 30 min to achieve the purpose of pore expansion, impurity removal and reduction of agglomeration. The ultrasonically pretreated halloysite nanotubes were centrifuged and dried at 80 ° C for use; 1 g of the acetylated lignin prepared in step 1) was added to 100 mL of dioxane aqueous solution (the volume ratio of dioxane to water was 4:1), and ultrasonic dispersion was performed at 150 W for 1 h to form a solution B, 1 g of the dried ultrasonically pretreated halloysite nanotubes was mixed with 100 mL of water to form a mixed solution A, and solution B was added to solution A under magnetic stirring at 400 r / min, and magnetic stirring was performed for 5 h. After ultrasonic treatment at 150 W for 30 min, the solid was centrifuged to remove the unabsorbed lignin, and the halloysite nanocomposite was obtained by drying at 60 ° C for 12 h.

[0079] 3) Take 1g of the halloysite nanocomposite prepared in step 2), add 50mL of dioxane aqueous solution (the volume ratio of dioxane to water is 4:1), mix ultrasonically at 150W for 1h, then homogenize at 12000r / min for 5min at room temperature, add 15mL of chitosan solution, 30mL of polyvinyl alcohol aqueous solution and 0.2mL of glycerol after homogenization, stir magnetically at 400r / min for 12h at room temperature to fully mix, then ultrasonically treat at 150W for 30min to remove bubbles in the solution, then cast into a 10cm×10cm mold, dry at 60℃ for 24h to form a film, and obtain the transparent UV-resistant composite film. Preparation of chitosan solution: 3g of chitosan is added to 100mL of 1% acetic acid aqueous solution to dissolve to obtain chitosan solution; preparation of polyvinyl alcohol aqueous solution: 4g of polyvinyl alcohol is added to 100mL of water to dissolve to obtain polyvinyl alcohol aqueous solution.

[0080] Example 2

[0081] This embodiment provides a method for preparing a transparent UV-resistant composite film, comprising the following steps:

[0082] 1) 1 g of dealkalized lignin sample dried to constant weight was added to a 50 mL beaker, followed by the addition of 11 mL of propionic anhydride / pyridine (the volume ratio of propionic anhydride to pyridine was 5:10) solution, and the mixture was stirred at room temperature at 600 r / min for 20 hours. After the reaction was completed, 500 mL of distilled water was added, and a solid residue was obtained by centrifugation. The solid residue was washed three times with distilled water and vacuum dried at 50° C. for 30 hours to obtain acetylated lignin. According to this method, 2 g of acetylated lignin was prepared for use;

[0083] 2) 3 g of halloysite nanotubes were placed in a 500 mL beaker, 8 mL of 11.9 mol / L hydrochloric acid aqueous solution and 450 mL of water were added, and the mixture was ultrasonically pretreated at 300 W for 30 min to achieve the purpose of pore expansion, impurity removal and reduction of agglomeration. The ultrasonically pretreated halloysite nanotubes were centrifuged and dried at 80 ° C for later use; 2 g of the acetylated lignin prepared in step 1) was added with 160 mL of dioxane aqueous solution (the volume ratio of dioxane to water was 4:1), and the mixture was ultrasonically dispersed at 150 W for 1 h to form a solution B, 1 g of the dried ultrasonically pretreated halloysite nanotubes was mixed with 80 mL of water to form a mixed solution A, and solution B was added to solution A under magnetic stirring at 600 r / min, and the mixture was magnetically stirred for 1 h. After ultrasonic treatment at 300 W for 1 h, the solid was centrifuged to remove the unabsorbed lignin, and the mixture was dried at 60 ° C for 12 h to obtain a halloysite nanocomposite.

[0084] 3) Take 1g of the halloysite nanocomposite prepared in step 2), add 60mL of dioxane aqueous solution (the volume ratio of dioxane to water is 4:1), mix at 300W ultrasonically for 1.5h, then homogenize at 24000r / min at room temperature for 5min, add 17mL of chitosan solution, 28mL of polyvinyl alcohol aqueous solution and 0.2mL of glycerol after homogenization, stir magnetically at 700r / min for 10h at room temperature to fully mix, then ultrasonically treat at 25W for 2h to remove bubbles in the solution, then cast into a 10cm×10cm mold, dry at 60℃ for 24h to form a film, and obtain the transparent UV-resistant composite film. Preparation of chitosan solution: 3g of chitosan is added to 100mL of 1% acetic acid aqueous solution to dissolve to obtain chitosan solution; preparation of polyvinyl alcohol aqueous solution: 4g of polyvinyl alcohol is added to 100mL of water to dissolve to obtain polyvinyl alcohol aqueous solution.

[0085] Example 3

[0086] This embodiment provides a method for preparing a transparent UV-resistant composite film, comprising the following steps:

[0087] 1) 1 g of dealkalized lignin sample dried to constant weight was added to a 50 mL beaker, followed by the addition of 15 mL of propionic anhydride / pyridine (the volume ratio of propionic anhydride to pyridine was 2:10) solution, and the mixture was stirred at 500 r / min for 26 hours at room temperature. After the reaction was completed, 200 mL of distilled water was added, and a solid residue was obtained by centrifugation. The solid residue was washed three times with distilled water and vacuum dried at 80 ° C for 10 hours to obtain acetylated lignin; 3 g of acetylated lignin was prepared according to this method for later use;

[0088] 2) 3 g of halloysite nanotubes were placed in a 500 mL beaker, 8 mL of 11.9 mol / L hydrochloric acid aqueous solution and 450 mL of water were added, and the mixture was ultrasonically pretreated at 150 W for 30 min to achieve the purpose of pore expansion, impurity removal and reduction of agglomeration. The ultrasonically pretreated halloysite nanotubes were centrifuged and dried at 80 ° C for later use; 3 g of the acetylated lignin prepared in step 1) was added with 150 mL of dioxane aqueous solution (the volume ratio of dioxane to water was 4:1), and the mixture was ultrasonically dispersed at 150 W for 1 h to form a solution B, 1 g of the dried ultrasonically pretreated halloysite nanotubes was mixed with 100 mL of water to form a mixed solution A, and solution B was added to solution A under magnetic stirring at 50 r / min, and the mixture was magnetically stirred for 24 h. After ultrasonic treatment at 25 W for 2 h, the solid was centrifuged to remove the unabsorbed lignin, and the mixture was dried at 60 ° C for 12 h to obtain a halloysite nanocomposite.

[0089] 3) Take 1g of the halloysite nanocomposite prepared in step 2), add 40mL of dioxane aqueous solution (the volume ratio of dioxane to water is 4:1), mix at 200W ultrasonically for 0.5h, then homogenize at 6000r / min at room temperature for 10min, add 13mL of chitosan solution, 32mL of polyvinyl alcohol aqueous solution and 0.3mL of glycerol after homogenization, stir at 500r / min magnetic force for 14h at room temperature to fully mix, then ultrasonically treat at 300W for 1h to remove bubbles in the solution, then cast into a 10cm×10cm mold, dry at 60℃ for 24h to form a film, and obtain the transparent UV-resistant composite film. Preparation of chitosan solution: 3g of chitosan is added to 100mL of 1% acetic acid aqueous solution to dissolve to obtain chitosan solution; preparation of polyvinyl alcohol aqueous solution: 4g of polyvinyl alcohol is added to 100mL of water to dissolve to obtain polyvinyl alcohol aqueous solution.

[0090] Comparative Example 1

[0091] This comparative example provides a method for preparing a transparent UV-resistant composite film, comprising the following steps:

[0092] Take 15mL chitosan solution, 30mL polyvinyl alcohol aqueous solution and 0.2mL glycerol, stir them with magnetic force at 400r / min for 12h at room temperature to mix them thoroughly, then ultrasonically treat them at 150W for 30min to remove bubbles in the solution, then cast them into a 10cm×10cm mold, and dry them at 60℃ for 24h to form a film, thus obtaining the transparent UV-resistant composite film. The preparation of chitosan solution: 3g chitosan is added to 100mL 1% acetic acid aqueous solution to dissolve to obtain chitosan solution; the preparation of polyvinyl alcohol aqueous solution: 4g polyvinyl alcohol is added to 100mL water to dissolve to obtain polyvinyl alcohol aqueous solution.

[0093] Comparative Example 2

[0094] This comparative example provides a method for preparing a composite film, comprising the following steps:

[0095] Take 1g of dealkalized lignin, add 50mL of dioxane aqueous solution (the volume ratio of dioxane to water is 4:1), mix ultrasonically at 150W for 1h, then homogenize at 12000r / min for 5min at room temperature, add 15mL of chitosan solution, 30mL of polyvinyl alcohol aqueous solution and 0.2mL of glycerol after homogenization, stir magnetically at 400r / min for 12h at room temperature to fully mix, then ultrasonically treat at 150W for 30min to remove bubbles in the solution, then cast into a 10cm×10cm mold, dry at 60℃ for 24h to form a film, and obtain the composite film. The preparation of chitosan solution: 3g of chitosan is added to 100mL of 1% acetic acid aqueous solution to dissolve to obtain chitosan solution; the preparation of polyvinyl alcohol aqueous solution: 4g of polyvinyl alcohol is added to 100mL of water to dissolve to obtain polyvinyl alcohol aqueous solution.

[0096] Comparative Example 3

[0097] This comparative example provides a method for preparing a composite film, comprising the following steps:

[0098] 1) 1 g of dealkalized lignin sample dried to constant weight was added to a 50 mL beaker, followed by the addition of 13 mL of propionic anhydride / pyridine (the volume ratio of propionic anhydride to pyridine was 3:10) solution, and the mixture was stirred at 400 r / min for 24 hours at room temperature. After the reaction was completed, 400 mL of distilled water was added, and a solid residue was obtained by centrifugation. The solid residue was washed three times with distilled water and vacuum dried at 60° C. for 24 hours to obtain acetylated lignin. 1 g of acetylated lignin was prepared according to this method for later use;

[0099] 2) Take 1g of the acetylated lignin prepared in step 1), add 50mL of dioxane aqueous solution (the volume ratio of dioxane to water is 4:1), mix at 150W ultrasonic for 1h, then homogenize at 12000r / min for 5min at room temperature, add 15mL of chitosan solution, 30mL of polyvinyl alcohol aqueous solution and 0.2mL of glycerol after homogenization, stir magnetically at 400r / min for 12h at room temperature to fully mix, then ultrasonically treat at 150W for 30min to remove bubbles in the solution, then cast into a 10cm×10cm mold, dry at 60℃ for 24h to form a film, and obtain the composite film. The preparation of chitosan solution: 3g of chitosan is added to 100mL of 1% acetic acid aqueous solution to dissolve to obtain chitosan solution; the preparation of polyvinyl alcohol aqueous solution: 4g of polyvinyl alcohol is added to 100mL of water to dissolve to obtain polyvinyl alcohol aqueous solution.

[0100] Comparative Example 4

[0101] This comparative example provides a method for preparing a composite film, comprising the following steps:

[0102] 1) 3 g of halloysite nanotubes were placed in a 500 mL beaker, 8 mL of 11.9 mol / L hydrochloric acid aqueous solution and 450 mL of water were added, and the mixture was ultrasonically pretreated at 150 W for 30 min to achieve the purpose of pore expansion, impurity removal and reduction of agglomeration. The ultrasonically pretreated halloysite nanotubes were centrifuged and dried at 80 ° C for later use; 1 g of the dried ultrasonically pretreated halloysite nanotubes was mixed with 100 mL of water to form a mixed solution A, which was stirred at 400 r / min magnetic stirring for 5 h. After ultrasonic treatment at 150 W for 30 min, the solid was centrifuged and dried at 60 ° C for 12 h to obtain a halloysite nano-treated product.

[0103] 3) Take 1g of the nano-treated halloysite prepared in step 1), add 50mL of dioxane aqueous solution (the volume ratio of dioxane to water is 4:1), mix at 150W ultrasonic for 1h, then homogenize at 12000r / min for 5min at room temperature, add 15mL of chitosan solution, 30mL of polyvinyl alcohol aqueous solution and 0.2mL of glycerol after homogenization, stir at 400r / min magnetic force for 12h at room temperature to fully mix, then ultrasonically treat at 150W for 30min to remove bubbles in the solution, then cast into a 10cm×10cm mold, dry at 60℃ for 24h to form a film, and obtain the composite film. The preparation of chitosan solution: 3g of chitosan is added to 100mL of 1% acetic acid aqueous solution to dissolve to obtain chitosan solution; the preparation of polyvinyl alcohol aqueous solution: 4g of polyvinyl alcohol is added to 100mL of water to dissolve to obtain polyvinyl alcohol aqueous solution.

[0104] Test Example 1

[0105] The microstructure of the dealkalized lignin and the acetylated lignin prepared in Example 1 was studied using a scanning electron microscope (SEM). Figure 1 shown. Figure 1 Figure a is the SEM image of dealkalized lignin. Figure 1 Figure b is a SEM image of the acetylated lignin prepared in Example 1. It can be seen that the surface of the acetylated lignin becomes smooth and small microsphere particles appear.

[0106] Test Example 2

[0107] The composite films obtained in Examples 1-3 and Comparative Examples 1-4 were tested, wherein the transparent UV-resistant composite film obtained in Example 1 was recorded as PC-HALG, the transparent UV-resistant composite film obtained in Example 2 was recorded as PC-2HALG, the transparent UV-resistant composite film obtained in Example 3 was recorded as PC-3HALG, the composite film obtained in Comparative Example 1 was recorded as PC, the composite film obtained in Comparative Example 2 was recorded as PC-LG, the composite film obtained in Comparative Example 3 was recorded as PC-ALG, and the composite film obtained in Comparative Example 4 was recorded as PC-HNTS. The specific tests are as follows:

[0108] 1. Fourier transform infrared spectroscopy (FT-IR) analysis of composite membrane

[0109] The structure of the composite membranes prepared in Example 1 and Comparative Examples 1-3 was analyzed by Fourier transform infrared spectroscopy (FT-IR). Figure 2 As shown. 3419cm -1 The broad peak at 3438 cm-1 corresponds to the hydroxyl groups in the phenolic and aliphatic groups. -1 The low intensity peak at 2943 cm-1 is caused by the acetylation reaction between lignin and each hydroxyl group. -1 The peak at 1265 cm is attributed to the CH skeleton vibration in the -CH2 and -CH3 groups, while the CH-CH deformation associated with the aromatic ring vibration appears at 1265 cm -1 、1423cm -1 and 1577cm -1 At 1737 cm, acetyl groups were also observed. -1 (Aliphatic C=O stretching of acetyl), attributed to the acetylation reaction to produce acetyl, which makes the peak shape wider. The acetyl group not only reduces the hydroxyl content in the lignin chain, but also destroys the hydrogen bonds between the lignin chains, thereby increasing the active space of the lignin molecular chain and reducing the aggregation of lignin molecules.

[0110] 2. Study on the anti-ultraviolet performance of composite films

[0111] The composite films prepared in Examples 1-3 and Comparative Examples 1-4 were tested using a UV-visible spectrophotometer, and the results of the transmittance of ultraviolet light at 200nm-400nm and the transmittance of visible light at 400-780nm are shown in Table 1. Figure 3 shown.

[0112] Table 1

[0113]

[0114] As can be seen in Table 1, the transmittance of the composite film obtained in Example 1 at 200nm-400nm is only 2.90%, which is lower than 5%, that is, the shielding performance of the composite film obtained in Example 1 in the ultraviolet band exceeds 95%, and the anti-ultraviolet performance is excellent. The transmittance of the composite film in Example 1 in the visible light range of 400nm-780nm reaches 78.39%, with high transparency. The composite film of Comparative Example 2 has a UV transmittance of less than 5% at 200-400nm, but the transmittance of visible light is low and the transparency is poor. The visible light transmittance of the composite films of Comparative Examples 1 and Comparative Example 4 reaches more than 60%, but its UV transmittance at 200-400nm reaches much higher than 5%. The composite film of Comparative Example 3 has a UV transmittance of 13.92% at 200-400nm, which does not meet the requirement of less than 5%, and the transmittance of visible light is also less than 60%. That is, the composite film obtained in the embodiment of the present application has a visible light transmittance of more than 60% (high transparency) within the wavelength range of 400-780 nm, while the ultraviolet light transmittance within the wavelength range of 200-400 nm is less than 5%.

[0115] 3. Bending test of composite film in different directions

[0116] The transparent UV-resistant composite film prepared in Example 1 was bent in different directions. Figure 4 It can be seen that the transparent UV-resistant composite film prepared in Example 1 exhibits good flexibility in all directions, and it completely maintains its original shape after the bending stress is released.

[0117] 4. Tensile strength and elongation test

[0118] The tensile strength and elongation of the composite films prepared in Examples 1-3 and Comparative Examples 1-4 were tested, and the mechanical properties of the film samples were tested using an intelligent electronic tensile machine to determine the tensile strength (TS) and elongation at break (EAB). Before measurement, the film was cut into 70mm×10mm rectangular sheets, and then the initial distance was set to 25mm and the measurement rate was set to 50mm / min. Five groups of samples were prepared for each group, and the test was repeated to calculate the average value. The thickness of the film was measured using a handheld electronic digital micrometer, and the average value was taken in mm. TS and EAB were calculated according to the following formulas:

[0119]

[0120] Wherein, F represents the tension at membrane breakage / N; b is the membrane width / mm; d is the membrane thickness in mm; L is the length of the membrane when it breaks / mm; L0 is the initial length of the membrane / mm.

[0121] The test results are shown in Table 2, wherein the tensile strength and elongation of the composite films prepared in Example 1 and Comparative Examples 1-3 are compared. Figure 5 shown.

[0122] Table 2

[0123] Tensile strength (mean) Elongation (mean) Example 1 75.84 104.23 Example 2 70.32 93.16 Example 3 67.58 90.44 Comparative Example 1 64.49 86.23 Comparative Example 2 37.51 58.65 Comparative Example 3 57.32 73.15 Comparative Example 4 65.23 89.24

[0124] When the film material is used as packaging, it should have sufficient mechanical strength and ductility. As shown in Table 2, the composite film prepared by adding lignin in Comparative Example 2 has poor mechanical properties and a tensile strength of 37.51 MPa due to the self-aggregation of lignin molecules compared to the composite film of Comparative Example 1. The tensile strength of the composite film obtained by adding modified acetylated lignin and halloysite nanotubes in Example 1 is 75.84 MPa, which is 102% higher than the tensile strength of the composite film of Comparative Example 2 (P<0.05). At the same time, the elongation at break of the composite film of Example 1 is also increased from 58.65% to 104.23% compared with the composite film of Comparative Example 2. It may be due to the characteristics of the halloysite nanofiller carrying negative charges on the outer surface, electrostatic interactions occur with the positively charged chitosan, increase the orderliness of the molecules, and at the same time, mix with polyvinyl alcohol containing a large number of hydroxyl groups, increase intermolecular interactions, form a strong hydrogen bond network structure, and reduce the aggregation of lignin molecules. It shows that the tensile strength and elongation at break of the specific transparent UV-proof film of the present invention are significantly enhanced, and the film has good mechanical properties.

[0125] 5. Biodegradable experimental diagram of composite film

[0126] The composite film prepared in Example 1 (PC-HALG film, 5×5 cm) and the composite film prepared in Comparative Example 1 (PC film, 5×5 cm) were placed in soil at a depth of about 5-10 cm to simulate the degradation process of the composite film under natural conditions, and an appropriate amount of water was sprayed to maintain its humidity. Samples were collected every 2 days. The degradation of the material was detected by recording the changes in the appearance of the composite film over time. The degradation process recorded was compared with Figure 6 As shown. Obviously, the PC-HALG membrane degrades rapidly in the soil due to the addition of acetylated lignin halloysite nanotubes, and the water absorption and swelling accelerates its degradation rate. The PC-HALG membrane of Example 1 can be almost completely degraded within 6 days. The results show that the PC-HALG membrane of Example 1 has less negative impact on the environment.

[0127] 6. Biosafety test diagram of composite membrane

[0128] The bean sprout seeds were placed in water and placed in a weak light indoors for 12 hours, and then moved to a grid plate for cultivation. The treatment group used the solution (PC-HALG membrane solution) before film casting in Example 1 mixed with water to form a water body with a PC-HALG membrane solution concentration of 1 mg / mL to cultivate the bean sprouts in the grid plate, and the control group used tap water for cultivation. The plant status at 0, 3, 6, and 9 days was photographed with a mobile camera, and the bean sprout growth parameters, including the average germination rate and average plant height, were calculated. The growth conditions are shown in Figure 2. Figure 7 There was no significant difference in the growth and color of the two kinds of sprouts in water and the PC-HALG composite membrane solution of Example 1, and the bean sprouts grew uniformly, proving that the PC-HALG composite membrane of Example 1 has good biosafety and is non-toxic and non-polluting.

[0129] 7. Chroma test of composite film

[0130] The composite films prepared in Examples 1-3 and Comparative Examples 1-4 were placed on a white standard plate and a handheld colorimeter (CM-2300d Konica Minolta) was used to measure the L*, a* and b* values, as shown in Table 3. L* (0-100) represents the trend from black to white; a* (-80-100) represents the trend from green to red; b* (-80-70) represents the trend from blue to yellow. Three measurements were randomly performed on each composite film, and the color difference value E was calculated, as shown in Table 3, and the calculation formula is as follows:

[0131]

[0132] Where ΔL*, Δa* and Δb* are the color differences between the sample and the white standard (the white standard has L*=97.62, a*=-0.15, b*=2.70). The actual color comparison diagram of the composite films prepared in Examples 1-3 and Comparative Examples 1-4 is shown in Figure 8 shown.

[0133] Table 3

[0134] Recorded as L* a* b* ΔE Comparative Example 1 PC <![CDATA[92.95±2.76 a ]]> <![CDATA[3.29±1.06 c ]]> <![CDATA[15.64±4.99 c ]]> <![CDATA[14.24±5.24 d ]]> Comparative Example 2 PC-LG <![CDATA[53.78±0.62 d ]]> <![CDATA[12.65±0.28 a ]]> <![CDATA[29.68±0.18 ab ]]> <![CDATA[52.89±0.49 a ]]> Comparative Example 3 PC-ALG <![CDATA[73.71±5.86 c ]]> <![CDATA[3.13±3.29 c ]]> <![CDATA[33.85±2.43 a ]]> <![CDATA[39.57±5.68 b ]]> Comparative Example 4 PC-HNTS <![CDATA[91.35±1.25 a ]]> <![CDATA[3.56±1.65 c ]]> <![CDATA[18.10±2.25 bc ]]> <![CDATA[23.60±1.25 c ]]> Example 1 PC-HALG <![CDATA[88.09±2.05 b ]]> <![CDATA[3.66±0.11 c ]]> <![CDATA[23.80±4.27 b ]]> <![CDATA[23.50±4.77 c ]]> Example 2 PC-2HALG <![CDATA[86.71±3.24 ab ]]> <![CDATA[4.25±3.34 ab ]]> <![CDATA[24.15±2.11 b ]]> <![CDATA[25.53±3.68 c ]]> Example 3 PC-3HALG <![CDATA[84.25±3.86 ab ]]> <![CDATA[5.41±2.26 b ]]> <![CDATA[27.32±1.43 b ]]> <![CDATA[36.23±2.35 b ]]>

[0135] Table 3 shows the color parameters of each composite film. Since lignin is dark brown, even if only 1wt% of lignin is added, the color parameters (L*, a*, b* and ΔE) of the composite film are significantly different (P<0.05). As shown in the figure, it can be clearly seen that the composite film of Comparative Example 2 has a low transparency, which may be due to the aggregation of lignin molecules leading to the formation of a larger structure, absorbing higher wavelengths of light, thereby increasing the absorption and opacity in the visible light range. Compared with the composite film of Comparative Example 2, the composite film obtained by adding acetylated lignin in Comparative Example 3 has significantly lower L* and a* values, indicating that the acetyl group successfully replaces the phenolic hydroxyl group, reducing the color of lignin, which is consistent with the above results. The composite film obtained in Example 1 has a 63.79% higher brightness L* than the composite film of Comparative Example 2, a* value is reduced by 255.3%, and the color difference ΔE is significantly different. It may be that the lower apparent density of the acetylated lignin sample can reduce the concentration of chromophores and auxochromes per unit volume at the macro level, and the acetylated lignin loaded by the halloysite nanotubes further reduces the aggregation of lignin molecules, so that the composite film obtained in Example 1 shows a lighter color. There is no significant difference in the L* and a* values ​​of the composite film of Example 1 and the composite film of Comparative Example 1, indicating that the transparency of the lignin-based composite film obtained in Example 1 of the present invention has been greatly improved.

[0136] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A transparent UV-proof composite film, characterized in that: The raw materials of the transparent UV-proof composite film include acetylated lignin, halloysite nanomaterials, chitosan and polyvinyl alcohol; The acetylated lignin is loaded on the halloysite nanomaterial.

2. A method for preparing a transparent UV-proof composite film, characterized in that: The method comprises the following preparation steps: 1) Preparing acetylated lignin; 2) loading the acetylated lignin prepared in step 1) onto a halloysite nanomaterial to obtain a halloysite nanocomposite; 3) Mixing the halloysite nanocomposite prepared in step 2) with chitosan solution and polyvinyl alcohol solution, removing bubbles in the solution and then performing film-forming treatment to obtain the transparent UV-resistant composite film.

3. The method for preparing the transparent UV-resistant composite film according to claim 2, characterized in that: Step 2) comprises: mixing the halloysite nanomaterial, acetylated lignin and a solvent, and obtaining the halloysite nanocomposite after separation.

4. The method for preparing the transparent UV-resistant composite film according to claim 2 or 3, characterized in that: In step 2), the halloysite nanomaterial and water are first mixed to form a solution A, and then the acetylated lignin prepared in step 1) is dissolved in a dioxane aqueous solution to form a solution B, and then the solution B is added to the solution A and mixed, and the solid is separated after ultrasonic treatment to obtain a halloysite nanocomposite; Optionally, after the solid separation step, a drying step is also included; Optionally, before performing step 2), the step of acidifying the halloysite nanomaterial is also included; Optionally, before the halloysite nanomaterial and water are mixed, the step of placing the halloysite nanomaterial in a hydrochloric acid aqueous solution for ultrasonic pretreatment is also included; The ratio of the halloysite nanomaterial to water in step 2) is 1:(10-100), in g:mL; The dosage ratio of the acetylated lignin to the dioxane aqueous solution is 1:(10-100), in units of g:mL; The volume ratio of dioxane to water in the dioxane aqueous solution in step 2) is (1-9): (1-5); The mass ratio of the acetylated lignin in the solution B to the halloysite nanomaterial in the solution A is (1-5): (1-5); The ultrasonic power of the ultrasonic treatment in step 2) is 25-300W, and the ultrasonic treatment time is 0.5-2h; In step 2), solution B is added to solution A and the stirring speed is 50-600 r / min, and the mixing time is 0.5-24 h.

5. The method for preparing the transparent UV-resistant composite film according to any one of claims 2 to 4, characterized in that: In step 3), the halloysite nanocomposite prepared in step 2) is mixed with a dioxane aqueous solution, homogenized, and then mixed with a chitosan solution, a polyvinyl alcohol solution and glycerol, and subjected to ultrasonic treatment to remove bubbles in the solution and then subjected to film-forming treatment to obtain the transparent UV-resistant composite film.

6. The method for preparing the transparent UV-resistant composite film according to claim 5, characterized in that: The ratio of the halloysite nanocomposite to the dioxane aqueous solution in step 3) is 1:(40-60), in g:mL; The volume ratio of dioxane to water in the dioxane aqueous solution in step 3) is (1-5): (1-5); The homogenization time is 5-10 minutes, and the homogenization speed is 6000-24000r / min; The dosage ratio of the halloysite nanocomposite to the chitosan solution is 1:(13-17), in g:mL; The volume ratio of the chitosan solution, the polyvinyl alcohol solution and the glycerol is (13-17): (28-32): (0.1-0.3); The chitosan content of the chitosan solution is 1-5% by mass; The solvent in the chitosan solution is an acetic acid aqueous solution; the mass concentration of acetic acid in the acetic acid aqueous solution is 1-2%; The mass content of polyvinyl alcohol in the polyvinyl alcohol solution is 2-6%; The polyvinyl alcohol solution is a polyvinyl alcohol aqueous solution; Optionally, the film forming process includes casting and drying.

7. The method for preparing the transparent UV-resistant composite film according to any one of claims 2 to 6, characterized in that: In step 1), lignin is added to a propionic anhydride / pyridine solution and stirred for reaction. After the reaction is completed, water is added and the solid is separated to obtain acetylated lignin.

8. The method for preparing the transparent UV-resistant composite film according to claim 7, characterized in that: The dosage ratio of the lignin to the propionic anhydride / pyridine solution is 1:(11-15), in units of g:mL; The volume ratio of propionic anhydride to pyridine in the propionic anhydride / pyridine solution is (2-5):10; The stirring reaction speed is 400-600r / min, and the stirring reaction time is 20-26h; Optionally, the volume ratio of water to propionic anhydride / pyridine solution is (200-500):(11-15).

9. Use of the transparent UV-proof composite film according to claim 1 or the transparent UV-proof composite film prepared by the preparation method according to any one of claims 2 to 8 in UV-proof materials.

10. Use of the transparent UV-proof composite film according to claim 1 or the transparent UV-proof composite film prepared by the preparation method according to any one of claims 2 to 8 in food packaging materials.

Citation Information

Patent Citations

  • Lignin / PBAT composite film materials, their preparation methods and applications

    CN114474449B

  • Composite efficient adsorption material

    CN110215908A

  • Anti-ultraviolet nano-lignin composite membrane and preparation method thereof

    CN110564096A

  • Lignin-based carbon nano tube taking halloysite as template and preparation method of lignin-based carbon nano tube

    CN114956054A

  • Preparation method of HNTs loaded modified lignocellulose composite membrane and product

    CN116407963A

Cited By

  • Low-temperature polyolefin packaging film and preparation method thereof

    CN120792270A